Global justice and international economic law : opportunities and prospects - Carmody, Chi.; Garcia, Frank J.; Linarelli, John. (New York : Cambridge University Press, 2012)
'Global justice is one of the most important subjects in law and political theory today. What principles of justice might tell us about the actual practices of the WTO and other international economic institutions is of vital importance to states and their citizens. This volume reflects the results of a symposium held at Tillar House, the ASIL headquarters in Washington, DC, in November 2008 which brought together philosophers, legal scholars, and economists to discuss the problems of understanding international economic law from the standpoint of rights, justice, and economic efficiency. The book makes advances in developing the normative criterion for ecaluation and justifying the international economic legal order'--
Includes bibliographical references and index.
Keywords: Law -- Economic aspects -- Congresses; Distributive justice -- Congresses; Globalization and law -- Congresses; Foreign trade regulation -- Congresses